The Effect of Individual and Organizational Factors on Internal Auditors’ Moral Courage - Supriyadi Supriyadi (The Indonesian Journal of Accounting Research, 2020)
This research examines the effect of individual and organizational factors on internal auditors' moral courage to report fraud. The variables of individual factors – namely self-efficacy and resilience – and organizational factors – namely independence of the internal auditor's function and perceived audit committee support – are estimated to have positive effects on internal auditors' moral courage. With a multiple regression model based on questionnaire data from 59 respondents of internal auditors, this study found a positive effect of resilience, the independence of the internal auditor's function, and perceived audit committee support variables on the auditors' moral courage. However, the self-efficacy variable has a marginal negative effect on auditors' moral courage. This negative effect is thought to occur because of the nature of the self-efficacy variable as an individual variable. In contrast, the nature and type of internal audit assignments are a group task, so group solidarity can weaken self-efficacy due to a decrease in confidence to control situations and conditions independently. This study fills a gap in the internal auditor behavior literature by examining the causal effects of individual and organizational factors on the auditors' moral courage. The use of a parsimony multiple regression model involving relevant independent variables developed on a theoretical basis to test the causal effects is the methodological contribution of the study. Finally, this is the first study that measured the independence of the internal auditor's function by combining three critical aspects of an internal audit's authority, namely reporting, recruitment, and budgeting for the Indonesian context.